2018
DOI: 10.1017/s0031182018001841
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the superfamily Hemiuroidea (Platyhelminthes, Neodermata:Trematoda) based on partial 28S rDNA sequences

Abstract: In the present paper, the phylogenetic relationships between genera, subfamilies and families of the Hemiuroidea are explored. Twelve new sequences of 28 rDNA and data taken from GenBank (NSBI) on 43 species affiliated to 34 genera were included in the analysis. Most of the hemiuroidean trematodes form two highly supported clades (A and B), which are sister groups to each other.Hemipera manterijoined withGonocercaspp. with moderate statistical support. This clade is basal relative to the clades A and B. Сlade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 54 publications
2
28
1
Order By: Relevance
“…These studies have resulted in more stable classification schemes of genera within families and families within superfamilies of the subclass Digenea. For example, at the superfamily level, the studies of Microphalloidea (Tkach et al, 2003), Lepocreadioidea Odhner, 1905(Bray et al 2009, Brachylaimoidea (Heneberg et al, 2016) Echinostomatoidea Looss, 1899 (Tkach et al, 2016), and the recent study of Hemiuroidea by Sokolov et al (2018), can be highlighted. Additionally, at the family level, several studies have determined the inter-relationships among genera and the re-organization of subfamilies, such as the study by Tkach et al (2001) with Omphalometridae Looss, 1899 by Choudhury et al (2007) Atopkin et al (2019) with Haploporidae.…”
Section: Journal Of Helminthology 271mentioning
confidence: 99%
“…These studies have resulted in more stable classification schemes of genera within families and families within superfamilies of the subclass Digenea. For example, at the superfamily level, the studies of Microphalloidea (Tkach et al, 2003), Lepocreadioidea Odhner, 1905(Bray et al 2009, Brachylaimoidea (Heneberg et al, 2016) Echinostomatoidea Looss, 1899 (Tkach et al, 2016), and the recent study of Hemiuroidea by Sokolov et al (2018), can be highlighted. Additionally, at the family level, several studies have determined the inter-relationships among genera and the re-organization of subfamilies, such as the study by Tkach et al (2001) with Omphalometridae Looss, 1899 by Choudhury et al (2007) Atopkin et al (2019) with Haploporidae.…”
Section: Journal Of Helminthology 271mentioning
confidence: 99%
“…Telford [28] later realized, and regarded his species synonymous to P. cyanovitellosus. Further studies revealed the additional distribution sites of this species, i.e., Ishigaki Island and Kudaka Island, Japan [13,29]. The present case is the fifth and northernmost report of the species.…”
mentioning
confidence: 55%
“…All species reported so far from the abyssal plain are either lepocreadioids, fellodistomids or ‘derogenids’. The ‘derogenid’ is Gonocerca phycidis Manter, 1925 which is now considered a member of the family Gonocercidae ( Sokolov et al, 2016a , 2018a , 2019a ). The sequences of G. phycidis and two other Gonocerca Manter, 1925 species in Sokolov's study ( G. crassa Manter, 1934 and G. muraenolepisi Parukhin & Lyadov, 1979) are derived from Antarctic fishes and a close relationship is found between these species and G. oshoro Shimazu, 1970 from a macrourid in the northern Pacific Ocean giving further evidence of the relationship of Antarctic and deep-sea forms.…”
Section: Phylogenymentioning
confidence: 99%
“…The sequences of G. phycidis and two other Gonocerca Manter, 1925 species in Sokolov's study ( G. crassa Manter, 1934 and G. muraenolepisi Parukhin & Lyadov, 1979) are derived from Antarctic fishes and a close relationship is found between these species and G. oshoro Shimazu, 1970 from a macrourid in the northern Pacific Ocean giving further evidence of the relationship of Antarctic and deep-sea forms. Sokolov et al (2019a) found the Gonocercidae to be the basally derived group of the Hemiuroidea. This study presents a superfamily-wide molecular phylogeny which includes only a few deep-sea forms.…”
Section: Phylogenymentioning
confidence: 99%